Picture-based crop monitoring adopted by six institutions (private-sector insurance companies and associated partners) to improve agricultural insurance and financing services in India, Kenya and Ethiopia - CGIAR Research Program on Policies, Institutions, and Markets (2020)
Picture-Based Insurance provides affordable high-quality crop insurance by using smartphone images of smallholders’ crops. PIM research has led to large-scale testing and adoption of picture-based crop monitoring by private-sector insurance companies and associated partners HDFC ERGO General Insurance (India), Dvara E-Registry (India), Government of India, ACRE Africa (Kenya), R4 Rural Resilience Initiative (Ethiopia) and Centre for Agriculture and Bioscience International (CABI) (India, Kenya), creating opportunities to strengthen crop insurance, financing and agro-advisories for millions of farmers.